A Pain in the Butt: The Association Between Endo-Parasite Diversity and Horn Growth in Rocky Mountain Bighorn Sheep - Tanisha C. Henry; Samridhi Rijal; Joana Alves; Peter Neuhaus; Susan Kutz; Kathreen E. Ruckstuhl (Pathogens)
(1) Background: Parasites can significantly impact growth, reproductive success, and the development of secondary sexual characteristics in various species. Our study investigated the effect of gastrointestinal and lungworm parasite infections on the total annual horn growth of male bighorn sheep (Ovis canadensis canadensis) in Sheep River Provincial Park, Alberta, Canada. (2) Methods: We collected fecal samples of individually marked male bighorns over two years to investigate parasite egg and oocyst numbers and parasite diversity in feces, and how these could potentially affect their annual horn growth. (3) Results: We found that parasite species richness, year, age class, and the interaction between age class and species richness were significant predictors of horn growth, while individual parasite species did not have a significant effect. Notably, parasite species richness positively affected horn growth in young males, whereas it did not predict horn growth in adult and old males. (4) Conclusions: One possible explanation is that young males might prioritize resources for body and horn growth, potentially at the expense of immunity or parasite resistance. Our finding contradicts the idea of parasite-mediated sexual selection, where traits like bright plumage signal good health and parasite resistance.